One-step NGS molecular analysis of the CFTR gene on newborn dried blood spots gives a higher diagnostic sensitivity in affected and carrier subjects: A pilot study - Nunziato, Marcella; Starnone, Flavio; Giordano, Sonia; D'Antonio, Marcella; Scognamiglio, Domenico; Esposito, Maria Valeria; Correra, Antonio; Di Maggio, Federica; D'Argenio, Valeria; Luca Scaglione, Giovanni; Castaldo, Giuseppe; Salvatore, Francesco (Clinica chimica acta, 2024)
Cystic fibrosis is the most common hereditary recessive disease with an incidence of about 1:2500/3000. It has long been known that the disease is caused by deleterious mutations in the CFTR gene. Conventionally, the disease is diagnosed in several phases. The analysis of all the possible disease-causing molecular alterations is time consuming and may not lead to a definitive diagnosis in several cases. Consequently, we propose, in this paper, a rapid sequencing method that, in a single procedural asset, reveals the presence of small mutations and also the copy number variants (CNVs) from the DNA extracted from the Guthrie Spot. We first sequenced 30 blood spots, then we validated the method on 100 spots that underwent both traditional analyses and this complete NGS sequencing, and lastly, we tested the strategy on patients who normally do not reach the molecular sequencing step because of low level of Immune-Reactive Trypsinogen. Using this procedure, we identified 97 variants in the CFTR gene of our samples and 6 CNVs. Notably, the significant data were obtained in the group of patients with borderline or negative IRT who routinely would not undergo molecular testing. We also identified 6 carriers of "disease-causing" variants. This method is very robust. Indeed, there was a 100% concordance with Sanger sequencing validation, and 6 mutation carriers were identified who normally escaped molecular testing with actual conventional procedure. There were also 3 duplications of almost the entire gene in heterozygosity, which were not seen with traditional methods. Being quick and easy to perform, we suggest that complete sequencing of the CFTR gene, as in this study be considered for all newborns.